A contemporary concept of the value(s)-added food and agriculture sector and rural development. Issue 2 (15th March 2021) - Clark, Jill K.; Jablonski, Becca B.R.; Inwood, Shoshanah; Irish, Aiden; Freedgood, Julia
ABSTRACT: The changing structure of agriculture strains the historically close relationship between commodity agriculture and rural development. Meanwhile, growth in consumer interest for differentiated, value-added products has the potential to create community economic development opportunities. However, the evidence regarding the benefit of value-added programs for broader community wealth is mixed. We argue that the mixed findings result, in part, from differences in how "value-added" is defined. Value-added agriculture has been conceptualized in many ways. Taking a US-focused approach, we first review four main concepts: value-added, short food supply chain, values-based supply chain, and civic agriculture. Building on these, we present our definition of a value(s)-added food and agriculture sector, incorporating three features: (1) Consumers make purchases that simultaneously provide utility and enable a price premium; (2) the shared principles among firms and their relational arrangement support the distribution of the value, and thus the premium, across the chain and between owners and employees (the use of "principles" or "values" prompts the "(s)" in our definition); and (3) supply chain actors have a demonstrated commitment to the community. We discuss how this definition contributes to debates in, and has implications for, community economic development policy.